The Influence Of Motivation, Job Training, And Information Technology To Performance Of Employee Maxone Hotel & Delia Resort Makassar - Azis, Azhar Asy’ari; Muhibuddin, Andi; Saleh, Muhammad Yusuf (Indonesian Journal of Business and Management, 2018)
This study aims to determine the effect of motivation, job training and information technology on the performance of employees of Maxone Hotel & Resort Delia Makassar. The research method used is a quantitative method, the data of this study were analyzed using SPSS 24 software. The number of samples in this study were 73 employees. The results showed that motivation had a positive and significant effect on employee performance with unstandardized coefficients 0,371 with tcount 3,42 8> t-table 0,235 with a significance level of 0,001 < 0,05; Job training has a negative but not significant effect on employee performance with unstandardized coefficients 0.168 with t-count of 1.549 > t-table 0.235 with a significance level of 0.126 > 0.05; Information technology has a positive and significant effect on employee performance with unstandardized coefficients 1,549 with t-count 3,727 > t-table 0,235 with a significance level of 0,000 < 0,05; motivation, job training and information technology have a positive and significant effect on employee performance with F-count 46.734 > F-table 2.74 with a significance level of 0.000 < ? 0.05.